Production of polysaccharidases in different carbon sources by Leucoagaricus gongylophorus Moller (Singer), the symbiotic fungus of the leaf-cutting ant Atta sexdens linnaeus - Silva, A.; Bacci, M.; Pagnocca, F. C.; Bueno, Osmar de Carvalho [UNESP]; Hebling, MJA (Springer, 2006)
Leucoagaricus gongylophorus, the fungus cultured by the leaf-cutting ant Atta sexdens, produces polysaccharidases that degrade leaf components by generating nutrients believed to be essential for ant nutrition. We evaluated pectinase, amylase, xylanase, and cellulase production by L. gongylophorus in laboratory cultures and found that polysaccharidases are produced during fungal growth on pectin, starch, cellulose, xylan, or glucose but not cellulase, whose production is inhibited during fungal growth on xylan. Pectin was the carbon source that best stimulated the production of enzymes, which showed that pectinase had the highest production activity of all of the carbon sources tested, indicating that the presence of pectin and the production of pectinase are key features for symbiotic nutrition on plant material. During growth on starch and cellulose, polysaccharidase production level was intermediate, although during growth on xylan and glucose, enzyme production was very low. We propose a possible profile of polysaccharide degradation inside the nest, where the fungus is cultured on the foliar substrate.